Application of 3D design method in design of underground mine development - WU Tao; LIU Bingfeng; LIN Jifei; DONG Juan; FENG Xinglong (Gong-kuang zidonghua, 2015)
In view of problem that it was difficult to quickly and effectively obtain the best mining scheme by using two-dimensional design method, application foundation of 3D design method, 'face + slicing', the creating of 3D roadway engineering models and statistical function of design objective were systematically introduced. 3D design method was used to design development system of an iron ore in Yunnan, and various schemes were compared and analyzed to determine the reasonable development scheme.